Anti-inflammatory activity of combined pods and seed extract of Parkia Speciosa on lipopolysaccharide-induced paw edema in rats - Y., Norazlin; N.D., Usamah; H., Wan Mas Salamah; A. Z., Alif; M. A. L., Qayyum; H., Hazilawati; M. N., M. Hezmee (Springer Nature, 2022)
This study provided a report on the selected medicinal use of Parkia speciosa Hassk or stink beans in terms of its anti-inflammatory activity. Previous studies related to its anti-inflammatory activity only focused on in vitro studies. Due to the lack of previous in vivo studies, the data in this study supported the findings by previous researchers and facilitated future drug discovery research.Lipopolysaccharide (LPS)-induced paw edema was studied in this article. Subplantar injection of LPS, 0.1 ml with the concentration of 100 µg/100 µL into the paw of rats elicited an acute inflammatory response characterized by an increase in paw thickness and infiltration of inflammatory cells. Paw edema thickness, total white blood cells (TWBC) number and its differential, erythron parameters, plasma biochemistry, and histology of the paw were evaluated. All parameters of inflammation (paw thickness, infiltration of inflammatory cells, TWBC numbers and its differential, erythron parameters, plasma biochemistry, and paw histology) were attenuated by the pre-treatment with P. speciosa extract. The results showed a significant reduction (p < 0.05) in the paw edema thickness for all doses of P. speciosa extract (100, 200, and 400 mg/kg) starting 5 h after lipopolysaccharide (LPS) injection, which was comparable to flunixin meglumine. Histological scoring of the inflammatory reaction and edematous lesion in the paws showed significant reduction (p < 0.05) in rats treated with three doses of P. speciosa extract compared to the negative control group. The findings concluded that P. speciosa extract possesses anti-inflammatory activity in rats.